The internationality of IFLA journal authors - Ocaya, Raissa Faye O.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
As the world becomes increasingly drawn into a single global community, it is important to have respect and appreciation for the multitude of perspectives that are present in order for the human race to live in peace and harmony with each other.
International journals, through their wide reach of readers, help foster or hinder this diversity depending on the true internationality (or the lack of it) of the content of their publication. It is thus important to determine how 'international' these journals really are. This study is an investigation of the journal of the International Federation of Library Associations from a publication period of 1975-2001 to determine their internationality or the extent to which they involve authors of different nations.
Through comparing the number of authors as they are grouped according to country/ world region/economic status and through the application of two formulas (Herfindahl-Hirschman and Entropy Coefficient) used in studying monopolies in markets, the researcher came up with the following findings: Although the IFLA journal publishes contributions from many countries, majority of the published articles were works of authors affiliated with Developed Countries, particularly those in Europe and North America, and more specifically, those hailing from the United Kingdom, the United States, and Canada.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: IFLA Journal; Library associations -- Societies, etc